Case Study: Progressive Muscle Relaxation to Reduce Head Pain in Elderly Hypertension Patient - Murdo Saputri, Widiastuti; Anindito, Teguh (CV. Dyoqu Publishing Management, 2025)
Background: Hypertension is one of the most common degenerative diseases suffered by the elderly, with headache as one of the common symptoms. Pharmacological management of headache pain often causes side effects, so that alternative non-pharmacological therapies are needed that are safe, inexpensive, and effective. Aims: This study aims to determine the effectiveness of progressive muscle relaxation intervention in reducing headache pain in elderly patients with hypertension. Methods: This study used a case study approach with participants of an elderly patient with hypertension at PPSLU Cepiring, Kendal. The intervention in the form of progressive muscle relaxation was carried out for six consecutive days. Data were collected through observation of blood pressure and pain scale before and after the intervention, as well as interviews on the subject's condition. Result: The results showed that the subject's blood pressure decreased from 158/100 mmHg to 140/90 mmHg. The headache pain scale also decreased from 6 to 2. In addition, the subject felt an increase in comfort, sleep quality, and emotional relaxation. Conclusion: Progressive muscle relaxation is proven effective as a nonpharmacological intervention in reducing head pain and blood pressure in elderly patients with hypertension. This technique can be integrated in gerontic nursing services to improve the quality of life of the elderly holistically.